A Li-Ion Battery Pack Level Degradation Simulator with Consideration of Thermal and Electrical Conditions. (6th January 2017) - Fukui, Masahiro; Hayakawa, Yukinori; Lin, Lei
Abstract : Li-ion battery pack is used for electric vehicles and distributed power systems as the basic unit of battery system. The proposed analysis scheme of the performance and degradation is executed by assembled battery level based on the calibration of the basic degradation trend of the primitive cells. This system is constructed by MATLAB and battery degradation of EV is analyzed practically.